Potency of cashew nut shell liquid in rumen modulation under different dietary conditions and indication of its surfactant action against rumen bacteria. Issue 1 (December 2017) - Oh, Seongjin; Suzuki, Yasuyuki; Hayashi, Shusuke; Suzuki, Yutaka; Koike, Satoshi; Kobayashi, Yasuo
Abstract Background Cashew nut shell liquid (CNSL) is an agricultural byproduct containing alkylphenols that has been shown to favorably change the rumen fermentation pattern only under experimentally fixed feeding conditions. Investigation of CNSL potency in rumen modulation under a variety of feeding regimens, and evidence leading to the understanding of CNSL action are obviously necessary for further CNSL applications. The objective of this study was to evaluate the potency of CNSL for rumen modulation under different dietary conditions, and to visually demonstrate its surfactant action against selected rumen bacteria. Methods Batch culture studies were carried out using various diets with 5 different forage to concentrate (F:C) ratios (9:1, 7:3, 5:5. 3:7 and 1:9). Strained rumen fluid was diluted with a buffer and incubated with each diet. Gas and short chain fatty acid (SCFA) profiles were characterized after 18 h incubation at 39 °C. Monensin was also evaluated as a reference additive under the same conditions. Four species of rumen bacteria were grown in pure culture and exposed to CNSL to determine their morphological sensitivity to the surfactant action of CNSL. Results CNSL supplementation decreased total gas production in diets with 5:5 and 3:7 F:C ratios, whereas the F:C ratio alone did not affect any gas production. Methane decrease by CNSL addition was more apparent in diets with 5:5, 3:7, and 1:9 F:C ratios. An interactive effect of CNSL and the F:C ratio was also observed for methane production. CNSL supplementation enhanced propionate production, while total SCFA production was not affected. Monensin decreased methane production but only in a diet with a 1:9 F:C ratio with increased propionate. Studies of pure cultures indicated that CNSL damaged the cell surface of hydrogen- and formate-producing bacteria, but did not change that of propionate-producing bacteria. Conclusion CNSL can selectively inhibit rumen bacteria through its surfactant action to lead fermentation toward less methane and more propionate production. As CNSL is effective over a wider range of dietary conditions for such modulation of rumen fermentation in comparison with monensin, this new additive candidate might be applied to ruminant animals for various production purposes and at various stages.